Covid-19 pandemic: Collective memory theory and the memory of older people - Souza, Joana Trengrouse Laignier de; Reis, Luciana Araújo dos (Seven Editora, 2023)
In the last three years, humanity has experienced a state of pandemic. This global event was the result of the emergence of the SARS-CoV-2 virus, responsible for the disease called COVID-19 (Coronavirus Infectious Disease-19), whose severity and potential for lethality was quickly recognized, especially for certain groups, such as the elderly population. In this context, social isolation was considered as a preventive measure. Although distant, the pandemic was a phenomenon of planetary dimensions and, in this way, experienced in the core of society, translating, therefore, into collective memory. For Halbwachs (1990), collective memory is strongly anchored, finding strength and duration, in a set of men and women who are unique individuals, but operate as members of a group. In this sense, we understand that the group of elderly people who experienced, although distant, the consequences of the pandemic for their well-being and health, have their memories anchored in social milestones that they share as a group. The Theory of Collective Memory, therefore, becomes paramount as a theoretical resource to understand these impacts. DOI:https://doi.org/10.56238/emerrelcovid19-026